Plectranthias cruentus, a new species of anthiadine perchlet (Teleostei: Serranidae) from the Lord Howe Rise, Tasman Sea - Gill, Anthony C.; Roberts, Clive D. (Zootaxa, 2020)
Plectranthias cruentus new species is described from the holotype and two paratypes collected off Ball’s Pyramid and a paratype from Lord Howe Island. It resembles P. pelicieri Randall & Shimizu 1994 in live coloration and most morphological details, including absence of predorsal scales anterior to the supratemporal commissure, but differs in having the fifth or sixth (versus third) dorsal-fin spine longest, at least some pectoral-fin rays branched (versus all unbranched), and inconspicuous (versus distinct) serrations on the interopercle. It also differs in live coloration details.